Improved research-scale foam generator design and performance characterization. (January 2016) - Harding, Brian; Zhang, Bin; Liu, Yi; Chen, Hao; Mannan, M. Sam
Abstract: The release of a cryogenic, flammable liquid, such as LNG, poses a threat to individuals in the area of the release as well as responders who attempt to limit the damage of the release. The most common mitigation technique is high-expansion foam which can be used to blanket the liquid, reducing the accumulation of flammable vapor above the pool through a number of different mechanisms. Despite the effectiveness of high-expansion foam blanketing, there are many aspects of the interaction between foam and LNG that are unknown. A lab-scale high-expansion foam generator has been developed to allow the study of those interactions. Additionally, the novel foam generator design addresses many of the drawbacks of industrial-scale foam generators and allows researchers better control of the foam, while producing foam at rates that are conducive to lab applications. Foam was produced using the generator and expansion ratio and foam stability were measured to determine the quality. The generator was able to produce foam with expansion ratio between 298 and 892 that collapsed at an average rate of 0.4 cm per minute. This quality of the foam is comparable to industrial-scale foam generators and the foam production rate is between 1.2 and 2.2 m 3 /min, which fits lab-scale needs. The foam generator can also be used with other types of non-firefighting foam, such as decontamination foam for chemical, biological, or nuclear decontamination. Highlights: New foam generator design based on NFPA 11. Production of high-expansion foam at lab-scale in experiments. Characterization of high-expansion foam in terms of expansion ratio and foam stability. Comparison of the new foam generator with industrial-scale generators.